Thomas Vaughan and the Rosicrucian Revival in England : 1648-1666 - Willard, Thomas (Aries Book Series., 2022)
In the first book-length study of Thomas Vaughan (1621-1666), Thomas Willard builds on recent scholarship in Western esotericism to show that his curious books offer much more than the lively quotations extracted from them. Treating more than alchemy and the Hermetic tradition, they develop themes from the synthesis of alchemy, magic, and Christian cabala, associated associated with the Rosicrucian movement that Vaughan introduced to English readers. His books respond to a moment in history when the breakdown in book censorship during the English Civil War allowed books with radical ideas to circulate, while political upheaval in the universities created audiences for new ideas. This book will be of interest to students of early modern religion, philosophy, science, and culture as seen by an intelligent and eloquent outsider.